Flashover characteristics of plastic cloth on ±800 kV HVDC transmission line. Issue 3 (February 2019) - Liu, Hui; Zhou, Chao; Shen, Qinghe; Yang, Bo; Sun, Xiaobin; Huang, Zhenning; Liu, Rong; Liu, Chuanbin
Abstract: In order to study the reasons for the restart failure after locking of the ±800kV HVDC transmission lines caused by the plastic cloth of the greenhouse, combined with a bipolar closure fault example of the ±800kV HVDC transmission line caused by a plastic cloth, the voltage and current time characteristics of the ±800 kV HVDC transmission line after failure are obtained through fault field investigation and fault recording analysis. Through plastic cloth contamination detection and linear equivalent test of ±800kV DC tolerance voltage, the necessary conditions for flashover and the time level of local burning to whole cloth breakage are obtained. The flashover, combustion and deionization process of plastic cloth are showed through linear equivalent 800kV DC voltage flashover test, which proves the possibility of three restart failure owing to the insufficient deionization as a result of the fact that fault current is large, the discharge channel is dispersed and the restart interval is short. Meanwhile, the flashover characteristics of plastic cloth of ±800kV HVDC transmission lines are obtained.